Analysis of the Drafting of the Electronic Information and Transactions Law (ITE Law) in the Perspective of Legal Drafting Science - Kaharuddin, Kaharuddin; Abrar, Muhammad Faishal; Ratuolinka, Diandra; Vianda, Nadya Luqyana; Tambunan, Natasya Christy Angelina (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This article describes and examines issues related to Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law) and its amendments, which were introduced with the aim of ensuring legal certainty for people conducting electronic transactions. The focus of this article is to examine the drafting of the ITE Law as stipulated in Law Number 12 of 2011, the application of principles in the drafting of the ITE Law, and the normative and implementative problems after the enactment of the ITE Law. The research used is normative legal research with a statute approach and conceptual approach. The legal materials in this study are divided into two categories, namely primary legal materials and secondary legal materials. The results of the study show that even though the formulation of the ITE Law is in accordance with the laws and regulations, its implementation still has many problems due to the non-implementation of several formal principles of the law and the large number of phrases with unclear boundaries.